Amir Sjarifoeddin, tempatnya dalam kekristenan dan perjuangan kemerdekaan Indonesia - Wellem, F. D. (Frederiek Djara) 1945- (Ut Omnes Unum Sint Institute, Center for Popular Education, 2009)
Biography of Amir Sjarifoeddin, the second Prime Minister of Indonesia during the country's national revolution, and his role in establishing the Indonesian independence and in the historical development of Christianity in Indonesia.